ANALISIS MULTIDIMENSIONAL SCALING DAN PENERAPANNYA PADA PEMETAAN KAB/KOTA DI PROVINSI SUMATERA BARAT BERDASARKAN JUMLAH PENDUDUK USIA KERJA TERDAMPAK COVID-19 - Dewi Safitri; Arnellis Arnellis (Journal of Mathematics UNP, 2021)
The COVID-19 pandemic became an epidemic throughout the country at the end of 2019 until now. The impact is not only on the health sector but also on the employment sector in Indonesia, one of which is West Sumatra. The perceived impacts include unemployment, temporary absence from work and a reducing working hours. This impact makes the economy of the community decline. The purpose of this research is to see how the districts/cities in the province of West Sumatra are mapped/grouped based on the number of working age residents affected by COVID-19 using multidimensional scaling analysis. So later it can be used as a reference for the government in the future. From the results of the mapping, three groups were formed. The largest number of working age residents affected by COVID-19 was Padang City, followed by Agam districts. With a stress value of 0.25% and R2 of 0,999 it shows that the multidimensional scaling analysis map obtained is acceptable.